Incapacity to Work Rate and Disability Rate in Traumatic Eye Disorders - Temiz, Dilek Doğan; Malkoç, Mehmet Ali; Demir, İbrahim; Şahan, Orhun; Özbay, Mehmet; Özsütçü, Mustafa (The Bulletin of Legal Medicine, 2023)
Objective: In this study, it was aimed to compare “incapacity to work rate scale” and “disability rate scale” in isolated eye traumas and to draw attention to differences between the scales.Methods: In our study, 605 files for which incapacity to work or disability rate was calculated only due to “eye defects” were examined in 2016, 2017 and 2018. Five hundred and ninety-two cases were analyzed retrospectively. The cases were evaluated in terms of parameters such as year of event, gender, age range, type of event, court types, and discretion. SPSS 21.0 statistical program was used to evaluate the data.Results: It is seen that average of “incapacity to work rate” is 29.24, “disability rate” is 21.56, “incapacity to work rate” is higher than “disability rate” in 455 cases (76.9%) and the “disability rate” is higher than “incapacity to work rate” in 38 cases (6.4%). In 99 cases (16.7%), both rates were not calculated. It was determined that there was a significant difference between rates in terms of both genders. In calculation of “incapacity to work rate”, it was determined that 8.28% of cases did not have exact equivalent of ratio and it was used with discretion, and this situation was all in diplopia cases.Conclusion: It was revealed that disability rate scale was more detailed and sensitive than “incapacity to work rate scale”, especially in diplopia, and that there was a difference between both scales in eye diseases in terms of methods and variables.
Keywords: Eye Traumas, Incapacity to Work Rate, Disability Rate.